Motion Graphic Sebagai Media Informasi Pada Mekanisme Pengajuan Permohonan Informasi Publik Di BP Batam Berbasis Online - Nur - Adila (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2022)
Currently, the development of the world of information technology is increasingly fast in the digital direction. These developments provide convenience for the community from its role in providing information. The Batam Concession Agency (BP) is a central agency that is committed to managing information by involving the community. BP Batam officially established the Information Management and Documentation Officer (PPID) BP Batam in 2010 by developing digitization through the PPID website. As time goes by, until now there are still batam people who do not know the mechanism for obtaining public information online. so in this study, motion graphics were made as a medium of information on the mechanism for submitting requests for public information at BP Batam in order to assist BP Batam Public Relations in providing information to the public. This research uses the Luther-Sutopo development method with several stages, namely, Concept, Design, Material Collecting, Assembly, Testing and Distribution. Based on the results of the analysis of alpha and beta testing on the delivery of motion graphic video information, the mechanism for submitting a request for public information at BP Batam has met the eligibility indicators for media elements, which resulted in 4.4 which included the category (SS) Strongly Agree and the information element 5 which included the category (SS) Strongly Agree and the results of the calculation of the respondents, namely the people of Batam with a value of 81,4 % which included the category (SS) Strongly Agree